Jespersen's cycle in Slovenian - Ilc, Gašper (Linguistica (Ljubljana), 2011)
The paper examines the syntactic status of the negative marker in standard Slovenian and its Pannonian dialects in terms of the grammaticalisation process known as Jespersen's cycle. Assuming that Jespersen's Cycle can be observed synchronically, the paper focusses on the correlation between the morpho-phonological strength of the negative marker and the syntactic derivation of negative clauses. The data analysis identifies at least three different stages of Jespersen's cycle in modern Slovenian: (i) the clitic-likenegation, (ii) the bipartite negation, and (iii) the adverb-like negation, the first occurring in standard Slovenian and the latter two in the Pannonian dialect group. In terms of the generative syntactic derivation, the analysis proposes that the negative marker occupies three different structural positions: (i) the head of the Negation phrase (clitic-like negation), (ii) the specifier of the Negation phrase (adverb-like negation) or (iii) both syntactic positions (bipartite negation). In addition, the paper explores the question whether the syntactic position of the negative marker determines the semantic interpretation of multiple occurrences of negative elements, in particular, the negative concord and the double negation interpretation. The analysis shows that in Slovenian the morpho-phonological properties of the negative marker and its structural position bear no consequences for the semantic interpretation of multiple occurrences of negative elements.
Keywords: cycle de Jespersen; denial; Jespersenov krog; jezikoslovje; linguistics; marqueurs de négation; négation; nikalni stavek; označevalci zanikanja; proposition négative; skladnja; Slovene; slovenščina; syntax; syntaxe; zanikanje